Dyplom honorowy w dowód uznania [...]. (Gdańsk : [s.n.], 1924)
Dyplom dla dyrygenta gdańskiego chóru Moniuszko Józefa Jachimczaka z 7.12.1924 r.
Fot. Gd.
Keywords: Gdański Chór Męski "Moniuszko".; Dyplomy -- Polska -- Gdańsk -- 1900-1945.; Gdańsk (Polska) -- 1920-1939 (Wolne Miasto) -- druki ulotne